Blisters and Loss of Epidermis in Patients With Lupus Erythematosus: A Clinicopathological Study of 22 Patients. Issue 46 (November 2015) - Merklen-Djafri, Carine; Bessis, Didier; Frances, Camille; Poulalhon, Nicolas; Debarbieux, Sébastien; Cordel, Nadège; Lipsker, Dan
Abstract : Abstract: The nosology of bullous lesions or equivalents (vesicles, erosions, and crusts) in patients with lupus erythematosus (LE) is rarely addressed. The primary aim of this study was to draw up a precise phenotypic inventory of such skin lesions; the secondary objective was to assess a potential relationship between the different types of loss of epidermis and extracutaneous lupus manifestations. We conducted a retrospective multicenter study including 22 patients with definite LE and bullous lesions or equivalents. All biopsies were reviewed. Patients were recruited in the dermatology departments of 6 centers. Patients were included if they met the diagnosis of systemic LE according to American College of Rheumatology and/or Systemic Lupus International Collaborating Clinics criteria or diagnosis of cutaneous LE based on classic clinical criteria and/or histological ascertainment of LE. Patients were recruited through clinician's memory and photographic collections. Three clinico-pathological patterns could be individualized. First, toxic epidermal necrolysis (TEN)-like, sheet-like, skin detachment; sun-exposure, mild mucosal involvement, and dermal mucin deposition allow differential diagnosis with classical Lyell syndrome. Second, vesiculo-bullae and/or crusting occurring on typical lesions of subacute cutaneous lupus erythematosus or chronic cutaneous lupus erythematosus. Third, tense vesicles and/or blisters with an underlying neutrophilic dermatosis and a usual response to dapsone. A careful analysis of 22 LE patients with epidermal detachment reveals 2 main pathomechanisms: a classic LE interface dermatitis, which can be hyperacute and lead to TEN-like skin detachment; and a neutrophilic dermatosis, with tense vesicles and/or blisters, including classic bullous LE.